Acute metabolic effects of exercise in bodybuilders using anabolic steroids. Issue 3 (September 1989) - McKillop, G; Ballantyne, F C; Borland, W; Ballantyne, D
Abstract : Four male bodybuilders who had started taking anabolic steroids were monitored during exercise. Most metabolic indicators were similar to bodybuilders not taking steroids; i.e. metabolic acidosis with little change in glucose. However, there is a marked elevation of creatine kinase.